The apartment - Steel, Danielle (New York : Dell Publishing Co., Inc., 2017)
Four friends sharing a beautiful loft apartment in New York City's Hell's Kitchen revel in the glamour of city life before new relationships, job opportunities, and surprising circumstances test the strength of their bond.
Keywords: CHICK LITERATURE